Cancer-Associated Fibroblasts Promote Vascular Invasion of Hepatocellular Carcinoma via Downregulating Decorin-integrin β1 Signaling - Zheng, Xiaobo; Wang, Peng; Li, Li; Yu, Jing; Yu, Chune; Xu, Liangliang; Li, Lian; Dai, Fuzhen; Feng, Lei; Zou, Hong; Chen, Xiaobo; Zhang, Ming; et al. (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) is a common malignancy worldwide, and the high ratio of recurrence and metastasis remains the main cause of its poor prognosis. Vascular invasion of HCC includes microvascular invasion (MVI) and portal vein tumor thrombosis (PVTT) and is regarded as a common roadmap of intrahepatic metastasis in HCC. However, the molecular mechanism underlying vascular invasion of HCC is largely unknown. Here, we analyzed the transcriptomes of primary tumors, PVTT tissues, and tumor tissues with or without MVI. We found that extracellular matrix-related pathways were involved in vascular invasion of HCC and that decorin secreted by cancer-associated fibroblasts was gradually downregulated from normal to tumor tissues and more so in PVTT tissues. We also established that low-level decorin expression is an independent risk factor for MVI and it is associated with a poor prognosis. Decorin downregulated integrin β1 and consequently inhibited HCC cell invasion and migration in vitro. Co-staining DCN and integrin β1 revealed that DCN dynamically regulated integrin β1 protein expression. Integrin β1 knockdown significantly inhibited HCC invasion and migration, and decorin combined with such knockdown synergistically augmented the anti-metastatic effects. Co-IP assay confirmed the direct interaction of decorin with integrin β1. Our findings showed that targeting cancer-associated fibroblast-related decorin is not only a promising strategy for inhibiting HCC vascular invasion and metastasis but also provides insight into the clinical treatment of patients with PVTT.